How and what to dance - D'Egville, Geoffrey (Bounty Books, 2008)
How & What to Dance guides you through the etiquette of the ballroom providing invaluable advice on elements such as costume, deportment, how to hold your partner and the discipline of dancing. Step-bystep instructions for all the dances are also included, with footstep diagrams to guide you through the Foxtrot, the Quick Step, the Charleston, the Tango and more.